Analisa Efektivitas Penerapan Sistem Informasi Akuntansi Persediaan Barang pada PT Indomakmur Inti Lestari - Saprudin; Hutasoit, Masri; Dewi, Sita; Aslah, Titi; Saragih, Rudi Hedianton (Media Ilmiah Akuntansi, 2025)
The purpose of this study is to determine how inventory management of merchandise is carried out at PT. Indomakmur. The implementation of Accounting Information Systems for inventory is expected to encourage improved performance and provide a positive impact on the company and related units. In addition, this system also supports smooth operations, especially in marketing activities, because the company can more easily identify market or consumer needs and demands. This study focuses on analyzing the effectiveness of the inventory accounting information system in preventing fraud at PT. Indomakmur Inti Lestari. The research method used is descriptive qualitative, with data collection techniques through observation and documentation, and data analysis using data reduction, data presentation, and drawing conclusions. The results of the study indicate that the inventory cycle of merchandise and the implementation of accounting information systems in the company have largely been running quite effectively, although there are still several aspects that are less than optimal.